Stability and Thermodynamics of Zinc Group Metals with Salicyloyl Urea - Sood, V.; Sud, D.; Pannu, B.S. (Asian Journal of Chemistry, 2010)
The proton ligand stability constant of salicyloyl urea and stability constants and thermodynamic functions of its complexes with Zn(II), Cd(II) and Hg(II) have been determined in methanol-water 20 : 80 (v/v) system. The effect of change of temperature and ionic strength have been studied.